REVELATION AND COMMUNITY: A CENTRAL FACTOR IN THE EXAMINATION OF THE DIVINE - Norbert Klaes (Journal of Dharma, 1978)
Revelation is the centrality of the community to which and in which God discloses Himself. How do the different religions look upon the human community in the light of the divine selfdisclosure? Is not the community itself an integral part of Revelation? How does the Community shape the religious experience and man’s response to God? I shall examine this point by taking Christianity and Hinduism as two divergent approaches to the same problem.